ANALISIS KEMAMPUAN TENDANGAN DEPAN PENCAK SILAT PERGURUAN TAPAK SUCI KOTA PALOPO: ANALISIS KEMAMPUAN TENDANGAN DEPAN PENCAK SILAT PERGURUAN TAPAK SUCI KOTA PALOPO - Ilyas, Muslim (Jurnal Ilmiah Spirit, 2026)
This study aims to determine the front kick ability of pencak silat athletes from the Tapak Suci School in Palopo City. This study used a quantitative approach with a descriptive approach. The sample size for this study was 30 athletes, selected using a total sampling technique. The instrument used was a front kick test developed by Juhansyah Lubis. Data analysis techniques used descriptive statistics in the form of averages, maximum values, minimum values, standard deviations, and frequency distributions and percentages. The results showed that the front kick ability of pencak silat athletes from the Tapak Suci School in Palopo City had an average score of 92.34, which is in the good category, with a minimum score of 85.66 and a maximum score of 98.66. The standard deviation value of 3.77 indicates relatively homogeneous athlete abilities. The frequency distribution results indicate that the majority of athletes were in the good to excellent category. Based on the results of this study, it can be concluded that the front kick ability of pencak silat athletes from the Tapak Suci School in Palopo City is generally in the good category, but not yet fully evenly distributed. Therefore, a more targeted and specific training program is needed to optimally improve front kick technique.